Evaluating the Implementation of COSO-Based Internal Control in Operating Cost Control: A Case Study at PT Barru Barakah Properti - Warnila; Azwar Anwar; Nurafni Oktaviyah (Faculty of Economics dan Business, Atma Jaya Makassar University, 2026)
This study aims to evaluate the implementation of COSO-based internal control in supporting operating cost control at PT Barru Barakah Properti. This research employs a descriptive qualitative case study approach. Data were collected through semi-structured interviews, documentation, and observation involving internal parties from the finance, accounting, administration, and operational departments. Data validity was strengthened through source and technique triangulation by comparing interview findings with company documents and field observations. The analysis was conducted based on the five components of the COSO Framework, namely control environment, risk assessment, control activities, information and communication, and monitoring. The findings show that the company has implemented control environment, control activities, and information and communication components through organizational structure, authorization procedures, supporting documents, and routine reporting mechanisms. However, risk assessment and monitoring have not been formally and systematically implemented, as risk identification, evaluation, and follow-up mechanisms remain informal and are not supported by written procedures or evaluation reports. These findings indicate that the company’s internal control system is still operationally oriented and has not fully functioned as an integrated control mechanism. This study contributes to the practical evaluation of COSO-based internal control in operating cost control, particularly in a property service company context.